2016
DOI: 10.1017/s1092852916000547
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of mixed features in bipolar disorder

Abstract: Mood episodes with Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5)-defined mixed features are highly prevalent in bipolar disorder (BD), affecting~40% of patients during the course of illness. Mixed states are associated with poorer clinical outcomes, greater treatment resistance, higher rates of comorbidity, more frequent mood episodes, and increased rates of suicide. The objectives of the current review are to identify, summarize, and synthesize studies assessing the efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…In this post hoc analysis of 3 pooled phase II/III randomized, double-blind, placebo-controlled trials in patients with bipolar depression, more than half of the patients (58.4%) met the criterion for concurrent manic symptoms (YMRS total score ≥4 at baseline); this is relatively consistent with previously reported prevalence rates for mixed symptoms, which can range from 11% to 70% depending on the study and criteria used. 8,9,11,12,16 In patients with concurrent manic symptoms, sleep and irritability items had the highest mean baseline scores; this is consistent with previous reports as sleep and irritability have been identified to be common manic symptoms occurring in patients with bipolar depression. 12,16,38 Previous reports have also identified that patients with bipolar depression and mixed symptoms are more likely to be female compared with patients without manic symptoms 12,16,36 ; however, in our analyses, the sex distributions were similar between patient subgroups.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this post hoc analysis of 3 pooled phase II/III randomized, double-blind, placebo-controlled trials in patients with bipolar depression, more than half of the patients (58.4%) met the criterion for concurrent manic symptoms (YMRS total score ≥4 at baseline); this is relatively consistent with previously reported prevalence rates for mixed symptoms, which can range from 11% to 70% depending on the study and criteria used. 8,9,11,12,16 In patients with concurrent manic symptoms, sleep and irritability items had the highest mean baseline scores; this is consistent with previous reports as sleep and irritability have been identified to be common manic symptoms occurring in patients with bipolar depression. 12,16,38 Previous reports have also identified that patients with bipolar depression and mixed symptoms are more likely to be female compared with patients without manic symptoms 12,16,36 ; however, in our analyses, the sex distributions were similar between patient subgroups.…”
Section: Discussionsupporting
confidence: 90%
“…12,16 Using this broader definition of "with mixed features" in patients with bipolar depression, several studies have suggested that atypical antipsychotics may be an effective treatment in this patient population [35][36][37] ; however, it should be noted that the majority of these studies have been performed post hoc. 8,9 Our analysis was designed in a similar manner; to be identified as having concurrent manic symptoms, patients had baseline YMRS total score ≥4 but without requiring any minimum number of manic symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations